Employee Performance Based on Work Environment, Motivation and Corporate Culture - Abd. Rasyid Syamsuri; Abd. Halim; Lukman Nasution; Julianto Hutasuhut; Adrial Falahi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of work environment, motivation and corporate culture on employee performance CV. Vulkanisir Ban Makmur Perbaungan Serdang Bedagai, North Sumatra. Data collection in this study was carried out through a survey approach with the type of explanatory research. The population that was sampled in this study were employees of CV. Vulkanisir Ban Makmur Perbaungan Serdang Bedagai North Sumatra with a total of 68 respondents. Data collection techniques were carried out by studying documentation and questionnaires. The data analysis tools used in this study were multiple linear regression analysis, hypothesis testing using a partial significant test (T test), simultaneous significant testing (F test), and testing the coefficient of determination (R2). The results showed that partially (T test) and simultaneously (F test) it was known that the work environment, motivation and corporate culture had a significant effect on the direction of a positive relationship on employee performance CV. Vulkanisir Ban Makmur Perbaungan Serdang Bedagai, North Sumatra. Analysis of the test with the coefficient of determination (R2) obtained a value of 0.556, which means 55.6% of the employee performance factors of CV. Vulkanisir Ban Makmur Perbaungan Serdang Bedagai North Sumatra can be explained by the work environment, motivation and corporate culture, while the remaining 44.4% is explained by other factors not examined in this study.